Attitudes and perceptions among Iraqi young adults towards organs donation and transplantation: A call for action - Ghaith Al-Abbasi; Ameer Al-Jasim (SAGE Publishing, 2020)
Background: Organs transplantation is the only treatment for end-stage organ failure. However, the disparity between organs availability and the number of patients in the waiting lists is widening globally, especially in Iraq for many reasons. This study aims to assess the level of attitudes and perceptions among Iraqi young adults towards organs donation and transplantation as the first study to be conducted in Iraq for such purpose. Methods: This observational study was conducted among 912 Iraqi young adults through a structured questionnaire which was disseminated among social media platforms. Participants consented before filling the questionnaire and their responses were analyzed to test the hypothesis of the study. Results: Most of the participants were females, Muslims and in their undergraduate level. Overall, 84.2% of the participants were willing to donate their organs after death and (97.9%) of them actually agreed to sign for organs donation. Most of those who were not willing to donate have no idea whether their religion approves it or not. There was no statistically significant difference in willingness to donate between different socioeconomic classes or residency areas. Conclusions: Most of the participants are convinced with donating their organs after death and are willing to sign for organ donation programs, advocating for initiating an official governmental transplant agency with multiple local committees distributed among health directorates all over the country managing it. The hesitancy to donate organs was attributed mostly to religious and associated with lack of knowledge issues, thus education might be the key to positive attitudes.